Manajemen Pendidikan di Wilayah Perbatasan NKRI-RDTL : Manajemen Keuangan dalam Pemenuhan Sarana Prasarana - Frengky Neolaka; Fitra Ramadhan; Fincensius Oetpah; Erlin Fatima Halek (Panthera : Jurnal Ilmiah Pendidikan Sains dan Terapan, 2026)
School financial management is a crucial factor in supporting the provision of educational facilities and infrastructure, particularly in border areas facing various resource constraints. This study aims to analyze the application of financial management in providing school facilities and infrastructure in the border area of ​​the Republic of Indonesia (NKRI) and the Republic of Timor-Leste (RDTL). The study employed a qualitative approach with a multiple case study design in four schools: Kota Baru Public Junior High School, St. Antonius Padua Sasi Junior High School, Noemuti Public Senior High School, and Fatumfaun Public Junior High School. Data were collected through in-depth interviews, observation, and documentation, then analyzed using data reduction, data presentation, and conclusion drawing techniques. The results show that the implementation of school financial management varies across schools, particularly in aspects of budget planning and funding source management. Noemuti Public Senior High School had the best financial management with a score of 96%, while Kota Baru Public Junior High School received the lowest score of 62%. In terms of facilities and infrastructure, Fatumfaun Public Junior High School received the highest score of 92%. Although basic learning facilities are relatively available, some supporting facilities are still limited. The findings of the study indicate that planned and transparent financial management plays a crucial role in supporting the provision of educational facilities and infrastructure in border areas.